2005
DOI: 10.1136/oem.2005.020057
|View full text |Cite
|
Sign up to set email alerts
|

Primary osteoarthritis of hip, knee, and hand in relation to occupational exposure

Abstract: Aim: To identify occupations with excess prevalence of osteoarthritis of the knee, hip, and hand in a nationwide survey and to compare occupations with and without excess prevalence with regard to biomechanical stresses and severity of osteoarthritis. Methods: Patients presenting with osteoarthritis of the knee, hip, or hand were recruited throughout France by their treating physician who collected information on history, including age at onset, occupation, and occupational stresses to joints. Severity was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 19 publications
(11 reference statements)
4
91
0
3
Order By: Relevance
“…Among the 19 studies (20 papers) eligible for this review, a majority (18,25,26,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(45)(46)(47)(48) were cross-sectional, followed by a prospective cohort (44) and a case-control study (24). The sample sizes included >1000 participants (26,(35)(36)(37)41), 500-1000 participants (25,33,38,39,42,43), 100-500 participants (18,24,34,40,(44)(45)(46)48), and <100 participants (47).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 19 studies (20 papers) eligible for this review, a majority (18,25,26,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(45)(46)(47)(48) were cross-sectional, followed by a prospective cohort (44) and a case-control study (24). The sample sizes included >1000 participants (26,(35)(36)(37)41), 500-1000 participants (25,33,38,39,42,43), 100-500 participants (18,24,34,40,(44)(45)(46)48), and <100 participants (47).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…The sample sizes included >1000 participants (26,(35)(36)(37)41), 500-1000 participants (25,33,38,39,42,43), 100-500 participants (18,24,34,40,(44)(45)(46)48), and <100 participants (47). The study populations included only men (39,40,(44)(45)(46)(47)(48), only women (18,(24)(25)38), or both men and women (26,(33)(34)(35)(36)(37)(41)(42)(43). The type of work seems a likely reason for not including both genders in some studies.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although physical activity is vital for joint health and may protect against osteoarthritis (OA), studies on some high-intensity sports and strenuous occupations have shown a relationship to OA (8,9). However, research on the relationship between hip and knee health and moderate and vigorous physical activities in the general popula-tion has not been consistent.…”
Section: Introductionmentioning
confidence: 97%